Freedom from frozen: the first British military use of lyophilised plasma in forward resuscitation. Issue 1 (22nd December 2014) - Gokhale, S G; Scorer, Thomas; Doughty, H
Abstract : Prehospital use of blood products may improve survival. However, transfusion support with frozen blood components is logistically burdensome and constrains the configuration of prehospital medical support. Alternatives to frozen plasma, including lyophilised plasma, offer the potential for advanced resuscitation in the prehospital environment. We describe the successful use of lyophilised plasma by a UK patrol in the prehospital environment during operations in Afghanistan in 2012 and reflect on recent military experience and the need for further developments.